What drives green experiential loyalty towards green restaurants?. Issue 5 (18th November 2019) - Wu, Hung-Che; Cheng, Ching-Chan; Ai, Chi-Han
Abstract : Purpose: The purpose of this paper is to use a multi-level model as a framework to examine the relationships among experiential quality, green emotional attachment, green image, green switching experience, green experiential satisfaction and green experiential loyalty for the green restaurant industry. Design/methodology/approach: The data used in this study were based on a sample of 515 customers at a green restaurant in Taipei City of Taiwan. Data were analyzed using structural equation modeling and hierarchical regression analysis. Findings: The findings identify that interaction quality, peer-to-peer quality, physical environment quality, outcome quality, enjoyment quality and management quality influence experiential quality, which in turn results in green emotional attachment and green image respectively. Experiential quality, green image and green switching experience influence green experiential satisfaction, which in turn results in green emotional attachment. Green loyalty is influenced by green emotional attachment, green image, green experiential satisfaction and green switching experience. Green image moderates the relationships between experiential quality, physical environment quality and outcome quality. Practical implications: To increase experiential quality and green emotional attachment, enhance green image, green experiential satisfaction and green loyalty and decrease green switching experience, the study findings will help green restaurant management develop and implement market-orientated service strategies. Originality/value: This is the first study to investigate the effects of experiential quality, green emotional attachment, green image, green switching experience and green experiential satisfaction on green experiential loyalty in a green restaurant setting.